Intercellular crosstalk between cancer cells and cancer-associated fibroblasts via exosomes in gastrointestinal tumors - Longyang Cao; Hong Ouyang (Frontiers in Oncology, 2024)
Gastrointestinal (GI) tumors are a significant global health threat, with high rates of morbidity and mortality. Exosomes contain various biologically active molecules like nucleic acids, proteins, and lipids and can serve as messengers for intercellular communication. They play critical roles in the exchange of information between tumor cells and the tumor microenvironment (TME). The TME consists of mesenchymal cells and components of the extracellular matrix (ECM), with fibroblasts being the most abundant cell type in the tumor mesenchyme. Cancer-associated fibroblasts (CAFs) are derived from normal fibroblasts and mesenchymal stem cells that are activated in the TME. CAFs can secrete exosomes to modulate cell proliferation, invasion, migration, drug resistance, and other biological processes in tumors. Additionally, tumor cells can manipulate the function and behavior of fibroblasts through direct cell-cell interactions. This review provides a summary of the intercellular crosstalk between GI tumor cells and CAFs through exosomes, along with potential underlying mechanisms.